Adsorption of gases (CO2, CH4) using novel porous materials (MOFs) - Rada, Zana Hassan (Curtin University, 2016)
This research focuses on the synthesis, characterization, and capability of the metal organic frameworks (MOFs) as a candidate adsorbent for storage and separation of greenhouses gases. The performance and effectiveness of various synthesized MOFs were explored for the selectivity of CO2/N2 and CO2/CH4. The research contributes to the advances in synthesis of different MOFs and their application for gas uptake. This has potential advantages than other materials for future environmental science and materials applications.